Ethanol from a biorefinery waste stream: Saccharification of amylase, protease and xylanase treated wheat bran. (1st May 2016) - Wood, Ian P.; Cook, Nicola M.; Wilson, David R.; Ryden, Peter; Robertson, James A.; Waldron, Keith W.
Highlights: Amylase, protease and xylanase treated wheat bran was pretreated at a range of severities. Compositional changes by pretreatment and hydrolysis monitored. Pre-extractions reduced furfural derivative production at lower severities. Single addition simultaneous saccharification and fermentation assessed. Abstract: Biorefining aims to exploit the full value of plant material by sequentially extracting and valorising its components. Many studies focus on the saccharification of virgin biomass sources, but it may be more efficient to pre-extract high-value components before hydrolysis to fermentable sugars. In the current study, a bran residue from de-starched, protein depleted and xylanase treated wheat bran has been subjected to hydrothermal pretreatment, saccharification and fermentation procedures to convert the residue to ethanol. The most effective pretreatment conditions (>190 °C, 10 min) and saccharification conditions were identified following bench-scale liquid hot water pretreatment. Pre-extraction of enzymatically-hydrolysable starch and xylan reduced the release of furfural production, particularly when lower pretreatment severities were used. Pilot-scale steam explosion of the lignocellulosic residue followed by cellulase treatment and conversion to ethanol at a high substrate concentration (19%) gave an ethanol titre of ≈25 g/L or a yield of 93% of the theoretical maximum.